The role of the Lajnat Al-Ta'rifbil-Islam of Kuwait in da'wah to non-muslim - Omeroglu, Nesim (Penerbit UTM Press, Universiti Teknologi Malaysia, 2014)
This research studies the role of the Lajnat al-Ta’rif bil-Islam of Kuwait in preaching Islam to the non-Muslims and the strategies adopted to succeed in da’wa programmes at the national level. However, the committee has been facing with negative perceptions. Therefore this study seeks to provide some suggestions that may help in the development of da’wa activities. This study aims at achieving the following objectives. Firstly, to identify the subject of da’wa (Islamic propagation) and its position in Islam. Secondly, to analyse the organization of the Lajnat al-Ta’rif bil-Islam of Kuwait and lastly, to evaluate strategies adopted by the Committee for Islamic Da’wa to success at the national level. This study employed qualitative research method by critically analyse related issues from books, scientific publications and documentations. It also utilises interview survey with agencies and relevance authorities in Kuwait. The study found that Islam gives particular attention on the importance of da’wa especially da’wa to the non-Muslim. This factor has been a key successful factor for the committee in carrying out mission through social, education, and cultural service activities. This approach is regarded as the best method, theoretically and practically, besides the latest preaching techniques that are in line with real world and at the same time can be imitated by da’wa bodies of others.